Fluoride intake from meals served in daycare centres in municipalities with different fluoride concentrations in the water supply - Tiano, Ana Valéria Pagliari [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Orlando [UNESP]; Saliba, Nemre Adas [UNESP]; Sumida, Dóris Hissako [UNESP] (My University, 2009)
Purpose: The aim of this study was (1) to determine the fluoride content in the meals served to children aged up to 36 months in daycare centres of two municipalities with different levels of fluoride in the water supply, (2) to calculate the mean fluoride ingested daily by the children when consuming those meals and (3) to analyse the contribution of this consumption to the development of dental fluorosis. Materials and Methods: Samples of the meals served to the children were collected during a whole week. The fluoride content of the samples of solid foods and milk was analysed using an ion-specific electrode combined with reference electrode after diffusion facilitated by hexamethyldisiloxane. Samples of beverages were buffered with an equal volume of total ionic strength adjustment buffer and analysed using a combined electrode. The results were compared using the Mann-Whitney test. Results: Mean fluoride contents of the meals were of 0.204 ± 0.179 and 0.322 ± 0.242 lg F/mL (P < 0.05), respectively, in the municipalities with low and adequate fluoride content. Daily fluoride intake in the former was 0.013 ± 0.003 mg/kg body weight/day and in the latter was 0.012 ± 0.001 mg/kg body weight/day (P > 0.05). Conclusions: The children were not exposed to dental fluorosis in the daycare centres. However, the risk cannot be ignored, considering the meals and the use of fluoridated dentifrices at home may also contribute to fluoride intake.
Keywords: Fluoride; Fluorosis; Oral health